Single nucleotide variants in the SCN1A gene and their relation to the development of type 3 familial hemiplegic migraine - Santos, Bárbara Prevital dos; Maschi, Bruna; Campos, Gabriela Rosa; Rossi, Giovanna Correa; Ribeiro, Giulia Eloah de Pádua; Volpato, Glória Maria Doroso; Vitturi, Júlia; Carvalho, Lara Schiavão de; Rosin, Larissa Carolina; Coelho, Letícia Amelotti; Soter Neto, Rubem; Bello, Valéria Aparecida; et al. (Headache Medicine, 2022)
IntroductionMigraine is a complex brain disorder that is influenced by different pathophysiological aspects such as inflammation, structural changes, and dysfunctions in multisensory processing. Recent studies have showed that possible mutations in genes that interfere with the excitability of ion channels linked to nociception are one of the key mechanisms for the development of a migraine. In this sense, it is known that familial hemiplegic migraine type 3 (FHM3) undergoes specific missense mutational influences on the SCN1A gene that encodes the α1 subunit of NAV1.1, a voltage-gated sodium channel present in the brain that demonstrates that the deregulation of the excitatory- inhibitory balance of these channels in specific circuits may come to characterize the pathogenic mechanism of FHM3.ObjectivesInvestigate the relation of single nucleotide variants (SNVs) on the SCN1A gene encoder of the a1 subunit of the NAV1.1 channel with the development of FHM3.MethodsNarrative review performed by active search in the digital databases Virtual Health Library (BVS), PubMed, SciElo and Google Scholar.DevelopmentMigraine pathophysiology involves the distribution of ions between intracellular and extracellular compartments, which shows the role of the ion channels in the disease. In this regard, there is an activation of the trigeminal vascular meningeal system by the NaV1.1 channels, which are expressed in Aδ fibers. Therefore, it is believed that mutations on genes that encodes the ion channels act in the development of migraine, mainly by the meninges, as they are densely innervated by trigeminal nerve endings. (To see the complete abstract, please, check out the PDF).